The effects of strength training on endurance performance and muscle characteristics - Bishop, D.; Jenkins, D. G.; MacKinnon, L. T.; McEniery, M.; Carey, M. F. (Medicine & Science in Sports & Exercise, 1999)
PURPOSE: The purpose of this study was to determine the effects of resistance training on endurance performance and selected muscle characteristics of female cyclists. METHODS: Twenty-one endurance-trained, female cyclists, aged 18-42 yr, were randomly assigned to either a resistance training (RT; N = 14) or a control group (CON; N = 7). Resistance training (2X x wk(-1)) consisted of five sets to failure (2-8 RM) of parallel squats for 12 wk. Before and immediately after the resistance-training period, all subjects completed an incremental cycle test to allow determination of both their lactate threshold (LT) and peak oxygen consumption VO2). In addition, endurance performance was assessed by average power output during a 1-h cycle test (OHT), and leg strength was measured by recording the subject's one repetition maximum (1 RM) concentric squat. Before and after the 12-wk training program, resting muscle was sampled by needle biopsy from m. vastus lateralis and analyzed for fiber type diameter, fiber type percentage, and the activities of 2-oxoglutarate dehydrogenase and phosphofructokinase. RESULTS: After the resistance training program, there was a significant increase in 1 RM concentric squat strength for RT (35.9%) but not for CON (3.7%) (P < 0.05). However, there were no significant changes in OHT performance, LT, VO2, muscle fiber characteristics, or enzyme activities in either group (P > 0.05). CONCLUSION: The present data suggest that increased leg strength does not improve cycle endurance performance in endurance-trained, female cyclists.